2020
DOI: 10.3889/oamjms.2020.4906
|View full text |Cite
|
Sign up to set email alerts
|

The Link between HLA-B Alleles and Causative Drugs in Vietnamese Patients with Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis

Abstract: BACKGROUND: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are severe cutaneous adverse drug reactions. Human leukocyte antigens (HLA) may play an important role in the pathogenesis of SJS/TEN. AIMS: This study aims to identify HLA-B alleles in Vietnamese patients with SJS/TEN and to investigate the possible link between HLA-B alleles and causative drugs. MATERIALS AND METHODS: Sixty patients including SJS (30 patients) and TEN (30 patients) were enrolled in a cross-sectional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The remaining 4467 studies were screened for title, abstract, and full text, and 64 potentially relevant studies were identified. Of the 64 studies that underwent data extraction, 3 studies described the same study population and were excluded from the meta-analysis. Furthermore, there were 23 studies that did not count the SJS/TEN associations at the patient level and thus were excluded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 4467 studies were screened for title, abstract, and full text, and 64 potentially relevant studies were identified. Of the 64 studies that underwent data extraction, 3 studies described the same study population and were excluded from the meta-analysis. Furthermore, there were 23 studies that did not count the SJS/TEN associations at the patient level and thus were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…In the end, the meta-analysis included 38 retrospective observational studies with 2917 patients from more than 20 countries . There were 16 studies from Asia (1298 patients), 14 studies from North America (932 patients), 4 studies from Europe (208 patients), 3 studies from Africa (437 patients), and 1 study from Australia (42 patients).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In SJS, HLA genetic variations contribute to its development by making the HLA molecule, bound with the culprit drug or a drug metabolite, susceptible to T‐cell recognition 1 . The presence of HLA‐B*58:01 alleles and its association in allopurinol‐induced SJS have been detected in multiple ethnicities, including Chinese, Thai, Korean, Vietnamese, and Japanese populations 3,5 . Given this association, genetic screening has been employed in several countries to limit the incidence of allopurinol‐induced SJS since 2012 3 .…”
Section: Figurementioning
confidence: 99%
“…1 The presence of HLA-B*58:01 alleles and its association in allopurinolinduced SJS have been detected in multiple ethnicities, including Chinese, Thai, Korean, Vietnamese, and Japanese populations. 3,5 Given this association, genetic screening has been employed in several countries to limit the incidence of allopurinol-induced SJS since 2012. 3 The present case demonstrates novel HLA alleles that may predispose Filipino patients to developing allopurinol-induced SJS.…”
mentioning
confidence: 99%